Study on Antifriction Corrosion-Resistant Nanocrystalline Diamond Coating of Parts - D. N. Okhlupin; A. V. Korolev; I. V. Sinev (Current Approaches in Science and Technology Research Vol. 14, 2021)
The article presents the results of an experimental study of the corrosion resistance of the ta-C double coating of parts by PVD method with intermediate and final surface polishing with a discrete tool. The influence of regime factors on the results of polishing the ta-C coating with a discrete tool is shown, and optimal processing modes are proposed. Tests of samples in a salt bath showed that the double ta-C coating by PVD method with intermediate and final polishing ensures the absence of corrosion and coating peeling